Expanding the Knowledge on Lignocellulolytic and Redox Enzymes of Worker and Soldier Castes from the Lower Termite Coptotermes gestroi - Franco Cairo, João P. L.; Carazzolle, Marcelo F.; Leonardo, Flávia C.; Mofatto, Luciana S.; Brenelli, Lívia B.; Gonçalves, Thiago A.; Uchima, Cristiane A.; Domingues, Romênia R.; Alvarez, Thabata M.; Tramontina, Robson; Vidal, Ramon O.; Costa, Fernando F.; et al. (Frontiers in Microbiology, 2016)
Termites are considered one of the most efficient decomposers of lignocelluloses on Earth due to their ability to produce, along with its microbial symbionts, a repertoire of carbohydrate-active enzymes (CAZymes). Recently, a set of Pro-oxidant, Antioxidant, and Detoxification enzymes (PAD) were also correlated with the metabolism of carbohydrates and lignin in termites. The lower termite Coptotermes gestroi is considered the main urban pest in Brazil, causing damage to wood constructions. Recently, analysis of the enzymatic repertoire of C. gestroi unveiled the presence of different CAZymes. Because the gene profile of CAZy/PAD enzymes endogenously synthesized by C. gestroi and also by their symbiotic protists remains unclear, the aim of this study was to explore the eukaryotic repertoire of these enzymes in worker and soldier castes of C. gestroi. Our findings showed that worker and soldier castes present similar repertoires of CAZy/PAD enzymes, and also confirmed that endo-glucanases (GH9) and beta-glucosidases (GH1) were the most important glycoside hydrolase families related to lignocellulose degradation in both castes. Classical cellulases such as exo-glucanases (GH7) and endo-glucanases (GH5 and GH45), as well as classical xylanases (GH10 and GH11), were found in both castes only taxonomically related to protists, highlighting the importance of symbiosis in C. gestroi. Moreover, our analysis revealed the presence of Auxiliary Activity enzyme families (AAs), which could be related to lignin modifications in termite digestomes. In conclusion, this report expanded the knowledge on genes and proteins related to CAZy/PAD enzymes from worker and soldier castes of lower termites, revealing new potential enzyme candidates for second-generation biofuel processes.